DIVERSITY, MORPHOMETRY, AND POPULATION ABUNDANCE OF SEA URCHIN (Tripneustes gratilla) IN NORTH LOMBOK - Victor David Nico Gultom (SEAMEO BIOTROP, 2025)
Article Highlights- The highest absolute abundance of sea urchin Tripneustes gratilla was observed in August 2023- In 2024, the low absolute abundance of Tripneustes gratilla and the decline of sea urchin species diversity in North Lombok prospectively indicated overharvesting.- The number of gleaners and the gleaning activity conducted by local villagers prospectively harm seagrass meadows, especially on Tripneustes gratilla abundance AbstractSea urchin Tripneustes gratilla is commonly found in tropical shallow water-seagrass beds and is consumed for its roe in Southeast Asia. This study recorded five sea urchin species in the study area: Tripneustes gratilla, Pseudoboletia maculata, Salmacis bicolor, Salmacis sphaeroides, and Maretia planulata, with T. gratilla being the most abundant. The highest absolute abundance of T. gratilla was observed in August 2023, at 0.30 ind./m2, while from May to July 2024, it declined to 0.02 ind./m2. The mean diameters of T. gratilla ranged from 37.59 mm to 44.16 mm between August and October 2023 and from 17.39 mm to 48.45 mm between May and July 2024, having wide range of the mean weight. In September 2023, sea urchin with a test diameter of 35.0 – 39.9 mm were the most frequent to be found. This study provided baseline data on T. gratilla harvested from the seagrass habitat by the local community in North Lombok and highlights the potential for overharvesting in the area.